Ensiklopedi Nurcholis Madjid : Pemikiran Islam di Kanvas Peradaban Jilid I - IV - MUNAWAR-RACHMAN, Budhy (Penyunting) (Mizan, 2006)
Ensiklopedi Nurcholis Madjid : Pemikiran Islam di Kanvas Peradaban Jilid I - IV